Viral Zoom Karen: attending to 'the scratch' with Mapping the Affective Turn in Education. Issue 2 (4th March 2023) - Gerth van den Berg, Sarah; Harris, Chinyere; Raja, Rozena
ABSTRACT: Mapping the Affective Turn in Education: Theory, Research, Pedagogy gathers nearly two dozen interviews, essays, and reflections on teaching and learning from leading scholars of affect theory and methodology, both within and outside the field of education and curriculum studies. We review this volume alongside a media 'scratch': viral recording of a virtual class interrupted by Grandma's accusations of bringing politics – Black Lives Matter – into English class, student denials, and a teacher's attempt to get the situation 'back on track'. Dernikos, Lesko, McCall, and Niccolini's introduction and chapters they compiled offer ways of reading the affective jumpiness, multiple resonances, and conflicting response-abilities in this scene. We probe the currents of shame; consequences of dysconsciousness; and movements of machinic affects in this media 'scratch' as we think about what the affective turn in education has afforded us over a year-long process of writing – and thinking – with this volume.